How robust are Holocene treeline simulations? A model–data comparison in the European Arctic treeline region - Fang, K.; Morris, J.L.; Salonen, S.; Miller, P.A.; Renssen, H.; Sykes, M.T.; Seppä, H. (Journal of Quaternary Science, 2013)
Treeline encroachments and retractions can provide global-scale feedbacks to the climate system, and treeline dynamics are therefore of great relevance for understanding global climate variability. To assess the accuracy of long-term treeline simulations based on the generalized dynamic vegetation model LPJ-GUESS, we simulate European Arctic treeline dynamics over the past 9000 years and compare the results with fossil-based reconstructions. The results show that while LPJ-GUESS is limited in its ability to capture species-level current treeline patterns and past dynamics, it is generally able to realistically simulate the Holocene coniferous treeline changes with a cutoff biomass carbon of 2Ckg m